Eine Evaluation des Hauses des Jugendrechts Leipzig Ziele, Erfolge, Herausforderungen - Bender, Rowenia; Krumma, Aileen; Neubert, Jenna; Hoffmann, Anja; Bolesta, Deliah; Führer, Jennifer; Asbrock, Frank (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This book documents a comprehensive evaluation of the 'Haus des Jugendrechts' (House of Juvenile Justice) in Leipzig. In this institution, youth welfare services, the police and the juvenile public prosecutor's office work together under one roof in order to optimise interagency cooperation and thus achieve a more effective approach to juvenile delinquency. The evaluation includes three focal points: the perspective of the staff, that of juvenile offenders and the analysis of statistical data from the police, the public prosecutor's office and the district court. The results are used to formulate recommendations for action for the house in Leipzig as well as for the establishment of further houses of juvenile justice. The evaluation was conducted by the Centre for Criminological Research in Saxony. With contributions by Frank Asbrock | Deliah Bolesta | Jennifer Führer | Aileen Krumma | Anja Hoffmann | Jenna Neubert